Dengue and its association with hepatic biomarkers: antiinflammatory action and utilization of paracetamol as a hepatotoxicity factor - Mateus, Adrielly Oliveira; Bezerra, Maria Clara Oliveira; Nicoletti, Sabrina de Araújo; Miranda, Gabriel Correia Nedir; de Freitas, Carmem Tainá Alves; Soares, Rafael Mesquita; Façanha, Samuel de Osterno; dos Santos, Emanuel Inácio; da Costa, Rafaella Iughetti; Nunes, Marília Porto Oliveira; Braga, Jéssica Maria de Bezerra; Nunes Filho, Júlio César Chaves; et al. (Brazilian Journal of Case Reports, 2022)
Dengue fever is a tropical infectious pathology caused by an arbovirus from the Flaviviridae family, the dengue virus goes through an initial replication in striated and smooth muscle cells. The bioindicators of hepatic functions are enzymes that detect lesions in the hepatocytes. Thrombocytopenia is one of the bioindicators of the key clinical manifestations in dengue patients. Besides the natural process of the platelets in the anti-inflammatory activity, the used drugs act and the auto medication overcharges hepatic functions due to the hepatotoxicity of non-opioid analgesics. Usually, the most used analgesic is paracetamol. The present article aims to associate hepatic biomarkers with the dengue infection and the hepatotoxicity caused by the indiscriminate use of anti-inflammatory drugs like paracetamol. As a research method, the literature review was utilized, with the utilization of scientific articles related to the theme, taken from electronic databases such as Scielo and Google Scholar. Aiming to associate dengue with hepatic biomarkers such as thrombocytopenia and hepatotoxicity caused by the anti-inflammatory drug known as paracetamol. It is important to highlight the relation between thrombocytopenia and dengue´s hemorrhage episodes, besides the hepatic overload caused by the indiscriminate use of paracetamol.